Broader Estimates of Gastrocnemius Activity Generated a More Representative Cocontraction Index: A Study in Pediatric Population - Maria Vinti; Manob Jyoti Saikia; John Donoghue; Stephane Mandigout; Maxence Compagnat; Karen L. Kerman (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2023)
The electromyography (EMG) cocontraction index (CCI) given by the antagonistic/agonistic Root Mean Square (RMS) amplitude ratio of the same muscle is a qualified biomarker used for spastic cocontraction quantification and management in cerebral palsy children. However, this normative EMG ratio is likely subject to a potential source of errors with biased estimates when measuring the gastrocnemius plantar flexors activity. Due to the uneven distribution of electrical activity within the muscle volume, cocontraction levels can be misestimated, if EMGs are obtained from the sole traditional bipolar sensor location recommended by SENIAM. This preliminary study, on 10 healthy children (mean age 10 yr), investigated whether surface EMG detected proximally and distally via two pairs of bipolar electrodes, within the medial gastrocnemius (MG), provides a significant difference in CCI estimates during non-dynamic (isometric dorsiflexion) and dynamic (swing phases of gait) conditions. Gait cycles were extracted from Inertial Measurement Unit sensors. Medial gastrocnemius activity was greater distally than proximally during plantar flexion when it acts as an agonist (~24±18%) and it was greater proximally during dorsiflexion (~23±9%) when it is acting as an antagonist. As a direct consequence, CCI estimates from the conventional sensor location were significantly different (~36%) from the CCIs computed by considering broader MG regions. This difference arose in all subjects during isometric efforts and in two of 10 healthy children during the swing phase of gait who presented cocontraction patterns ( $\text{p} < 0.05$ ). EMG bipolar sampling encompassing proximal and distal gastrocnemius muscle regions may reduce bias in CCI computation and provide a more representative and accurate cocontraction index that is especially important for comparisons to the diseased state.